Strategi Pembelajaran Al-Qur’an Hadis dalam Pendidikan Dasar Islam: Integrasi Filsafat Moral, Teori Pendidikan, dan Tantangan Implementasi - Sholehah, Aat Mar'atun; Nurhasanah Leni; Muhammad Abi Hasan (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
The learning of Al-Qur’an and Hadith plays a crucial role in shaping the morality and character of students in Islamic elementary education. However, at MI Mathla’ul Anwar Gunung Sugih, Lampung, a gap exists between the ideal goals and the practical implementation of learning, such as students' lack of focus during recitation, their tendency to avoid performing Dhuha prayers, and the minimal internalization of moral values in daily life. This study aims to analyze the effectiveness of Al-Qur’an and Hadith learning in shaping students' morality and to identify more integrative and applicable teaching strategies. Using a qualitative descriptive-analytical method, data were collected through observation, interviews, and literature review, then analyzed using Miles and Huberman's interactive model. The findings indicate that experience-based learning strategies, such as the habituation of congregational prayers, reflective discussions on Qur’anic verses and Hadith, and the active involvement of teachers in moral guidance, are more effective in internalizing Islamic values. Furthermore, the support of family and social environments also plays a crucial role in shaping children's character more comprehensively. Therefore, Al-Qur’an and Hadith learning functions not only as a transfer of religious knowledge but also as a means of moral transformation, forming students into religious, ethical individuals with high social awareness. The findings of this study are expected to contribute to the development of more effective religious education strategies in building students' character from an early age.